Morphometric Analysis of Patella and Patellar Ligament in the Cadavers of Nepalese Origin - Sah, Surendra Kumar; Pandey, Nivedita; Chaudhary, Deepak; Ghosh, Shubrato; Yadav, Sudeep Kumar (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: The patella is the largest sesamoid bone in the body which develops within the tendon of the quadriceps femoris muscle. The patellar ligament is the continuation of distal part of the quadriceps femoris which finally ranges from the tip of patella to the tibial tuberosity of the tibia. The objectives of the study was to establish the morphometry of the Patella and Patellar ligament in correlation with gender and prevalence of types of patella. MATERIALS AND METHODS: The present study was conducted at the department of Anatomy of Nobel Medical College, Biratnagar, Nepal from Jan 2018 to June 2021. Twenty-six well embalmed adult cadavers (n=52) of known sex (13 Females and 13 Males) without any gross damage to the lower limbs were considered for the study. RESULTS: Out of the 52 limbs studied, the mean value of the length of patella, width of patella, thickness of patella in male were respectively 36.23±4.20mm, 37.15±6.09mm, 17.00±1.87mm. In female the values were 33.53±4.80mm, 34.53±6.07mm, 16.00±1.95mm which are highly significantly (p<0.005). In contrast it was also observed that the length of patellar ligament did not showed the significance differences between the male 45.92mm and female 44.92mm (p>0.05). So from here we can conclude that the morphometry of the patella plays an important role in the gender determination. CONCLUSIONS: The obtained data will be useful for the Comparative anatomy, Anthropology, Forensic Science and Evolutionary biology, anthropological records in context of Nepal and reference for the Orthopaedic surgeons in conducting the Knee replacement surgery as well.